2018
DOI: 10.1016/j.still.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of natural forest results in a significant degradation of soil hydraulic properties in the highlands of Kenya

Abstract: Land use change, especially conversion of native forests can have large impacts on water resources. Large scale conversion of native forests to agricultural land has occurred in the last few decades in the Mau Forest region. To quantify and understand landscape hydrologic responses, this study aimed at evaluating the effects of land use on soil infiltration, saturated hydraulic conductivity, bulk density, sorptivity, and soil moisture retention. A total of 136 plots representing five different land uses (nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 45 publications
(47 reference statements)
5
39
0
Order By: Relevance
“…Converted land use types in our study were characterized by livestock trampling in grazing lands, tillage during land preparation and trampling by humans and vehicular traffic in tea and eucalyptus plantations. All of these activities were observed to change the soil hydrologic properties (Owuor et al 2018), which can alter CH 4 production and consumption. The increased soil bulk density and higher water content measured in the tea and eucalyptus plantations and grazing lands reduced oxygen and CH 4 diffusion and increased occurrence of anaerobic conditions in the soil so that the observed net CH 4 uptake at the soil surface decreases as CH 4 production is stimulated while CH 4 oxidation decreases (Jacinthe et al 2014).…”
Section: Tea Estatementioning
confidence: 99%
See 1 more Smart Citation
“…Converted land use types in our study were characterized by livestock trampling in grazing lands, tillage during land preparation and trampling by humans and vehicular traffic in tea and eucalyptus plantations. All of these activities were observed to change the soil hydrologic properties (Owuor et al 2018), which can alter CH 4 production and consumption. The increased soil bulk density and higher water content measured in the tea and eucalyptus plantations and grazing lands reduced oxygen and CH 4 diffusion and increased occurrence of anaerobic conditions in the soil so that the observed net CH 4 uptake at the soil surface decreases as CH 4 production is stimulated while CH 4 oxidation decreases (Jacinthe et al 2014).…”
Section: Tea Estatementioning
confidence: 99%
“…In upland forest soils, soil conditions favour the activity and growth of methanotrophs and therefore the methane oxidation process is dominant compared to production (Kravchenko 2017), as a result forests soils usually act as methane sinks. Soil tillage or animal trampling, typically associated with agriculture, can affect soil properties such as bulk density (Owuor et al 2018), which in turn reduces soil pore size and connectivity (Dexter 2004) and thus, gas diffusivity. This reduction in diffusivity can then cause lower CH 4 uptake compared to soils of natural ecosystems (Jacinthe et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This knowledge is essential in the tropics, where population growth puts significant 15 pressure on forests and water resources, but where little is known about the consequences of deforestation. Previous studies in the South-West Mau block of the Mau Forest Complex observed reduced infiltration rates in agricultural compared to forested land use types (Owuor et al, 2018). Furthermore, analysis of nitrate concentration-discharge relationships of rainfall events suggested more surface runoff in catchments dominated by smallholder agriculture or commercial tea and tree plantations than in a montane forest catchment (Jacobs et al, in review).…”
Section: Stable Water Isotopes ( 2 Hmentioning
confidence: 94%
“…In our case, the difference could be caused by differences in hydraulic conductivity. Pasture soils in our study area had a generally lower hydraulic conductivity ) due to soil compaction by animal trampling (Owuor et al, 2018). 30…”
mentioning
confidence: 87%
“…Although significant knowledge has been derived from specific African regions such as Kenya (i.e. Arias-Navarro et al 2016, Jacobs et al 2017, Ortiz-Gonzalo et al 2018, Owuor et al 2018, there is a general lack of ground-based observations to constrain both continental (Valentini et al 2014) and global GHG budgets (Marcolla et al 2017, Zhu et al 2018.…”
Section: Introductionmentioning
confidence: 99%